Vivências acadêmicas das mulheres negras e pobres na Universidade Estadual Vale do Acaraú - UVA - Dias, Luana da Silva (2024)
Historically, the feminine in a class society, such as the capitalist one, was not given a place of prestige and importance in the political-social constructions of public spaces, such as in politics and at the University. Added to this, the wounds of a slavery process lasting more than three hundred years marked the black people with the Brazilian State's absent look at the most basic needs of life, such as education, perpetuating a process of income, gender and racial inequality. With this in mind, the present research, as an objective, sought to analyze how the academic experience of poor black students at the Universidade Estadual Vale do Acaraú (UVA) is taking place, taking into account objective and subjective factors that directly impact their stay at the university. Higher Education, such as personal aspects, pedagogical practices, interpersonal relationships with peers and professors, as well as institutional support for these women to remain at university. Methodologically, this is research of an applied nature, intended when one wants to uncover practical problems, of the case study type, being exploratory, as it aimed to understand and illuminate an unknown reality, in a situated context, of a specific social group, black and poor women at UVA, marked by peculiarities and social conditions that permeate their experiences. As for the procedures, the research is bibliographic and documentary, as it is anchored in the analysis of articles, theses, dissertations and books on the subject, as well as documents to receive an analytical treatment, starting from a mixed approach, this is because qualitative, so from the subjective view of the women studied, whose primary data collection took place through semi-structured interviews, duly authorized by ethical perspectives, as well as quantitative, since the interview transcriptions were submitted to lexical and statistical analysis software of textual corpus, to then the results are interpreted qualitatively. Thus, understanding the construction of the right to education as a human right, in the context of a capitalist and democratic society, it is understood that access to Brazilian higher education for these women is marked by contrasts of class, race and gender inequalities and with the consequent action of the State in the advent of the creation of public policies, especially with the legal and institutional foundations of the Public Student Assistance Policy, however these are of a general nature. It turns out that when this context is analyzed from the perspective of reality, there is a need to maintain specific agendas and actions that direct and combat gender, race and class inequality within the university, in favor of the academic success of the plural women who enter, as they are intersectional in this economic system, affecting them in personal, interpersonal and pedagogical aspects, demanding specific institutional action. As a result, despite the recognition of the expansion of access to Brazilian higher education and the significant presence of black females in the country's universities, including UVA, which could give rise to an appearance of achieving social justice and the effectiveness of constitutional rights guaranteed by Federal Constitution of 1988, this finding did not eliminate, however, the difficulties in this environment regarding gender, race/ethnicity and social condition that hinder the dignified and healthy stay and the completion of graduation, especially for female, black people and poor in higher education. In this way, the need to construct coping strategies for the university in question is considered, such as specific university assistance policies to meet the intersectionalities of gender, race and class of the subject studied.